Evaluation of comorbidities in the SARS-CoV-2-related mortalities: A retrospective observation from a dedicated COVID-19 care hospital - Nisha Khanna; Shreekant Bharti; G Guralarasan; Surabhi; Tarun Kumar; Ruchi Sinha; Punam P Bhadani (Journal of Family Medicine and Primary Care, 2024)
Since its discovery in Wuhan, China, in December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread rapidly around the world with being declared a pandemic in March 2020 by the World Health Organization (WHO). Comorbidities are one of the most concerning clinical considerations for mortality. Materials and Methods: This was a retrospective observational study conducted at the All India Institute of Medical Sciences in Patna, Bihar, from June 2020 to December 2020. It included adult patients who succumbed to coronavirus disease 2019 (COVID-19) during this period, and their relevant information, such as demographic information hospital stay duration, haematological parameters and comorbidities, was gathered. Results: The mean age of the study group was 63.5 (11.8) years. Of 150 cases, 126 men (about 84 per cent) and 24 women were involved (16 per cent). In our study, hypertension (HTN) was shown to be the most frequent comorbidity at 68.7% (103/150), followed by diabetes mellitus (DM) at 61.3% (92/150). The most prevalent haematological disorder identified in our investigation was anaemia and leucocytosis. Conclusion: The categorisation of patients who would need extra measures including early hospitalisation, heightened monitoring and intense therapy would be made easier by identifying patient traits and conditions.